Polymorphisms, in the Tnfa gene of different inbred mouse strains - Iraqi, F.A.; Teale, A.J. (Springer, 1999)
In view of the Tnfa gene location within the major histocompatibility (MHC) region and reports of its importance in disease protection activity, this paper examines the TNF a genes of a number of different mouse strains which were known to be of different disease response phenotypes. Twelve inbred mouse strains were studied. In a separate study, the repeat length in the (CA) n microsatellite located within the Tnfa promoter region of these 12 inbred mouse strains was determined, High relative molecular mass genomic (chramosomal) DNA of the inbred mouse strains was obtained from the Jackson Laboratory. The results of the study shows that pCR-RFLps were not detected in the promoter region. Two haplotypes were defined in the first intron and three haplotypes could be defined in 3 UTR in the 12 strains based on PCR-RFLP genotypes and, moreover, these were not strictly concordant with serologically defined H2 haplotypes.